Presisi Application Innovation In Manufacturing Services Online-Based Police Record Certificate (Skck) (Case Study At Jombang Police Station) - Annisa Anastasia; Oktarizka Reviandani (UNIVERSITAS PAKUAN, 2024)
According to Law No. 2 of 2002 Article 13, the main tasks of POLRI are to provide protection, shelter, and services to the community, including the service of making a SKCK. However, the SKCK process is often considered complicated and time-consuming. To overcome these problems, POLRI introduced an online SKCK service innovation through the PRESISI application in all Police agencies, including Polres Jombang to make it easier for the public to take care of SKCK and at the same time cut a little bureaucracy in Indonesia. This is expected to speed up and simplify SKCK processing. This study aims to determine and analyze the innovation of online-based SKCK services at Polres Jombang using the theory of digital public service innovation according to Bertot et al (2016). This type of research is qualitative research with a descriptive approach to provide a broad description of the object under study, especially innovations in online-based SKCK services at Polres Jombang. The results showed that the innovation of online SKCK making services as a whole can be said to be successful because it facilitates the community in the SKCK application process. However, in the process of filling in data on Presisi there are still shortcomings in predictive analysis related to the needs of citizens for SKCK applications in the application, and the lack of socialization from POLRI also contributes to the lack of understanding of citizens regarding this online SKCK service.